Cirrhosis but not neutropenia is associated with the development of infection in patients with chronic hepatitis C undergoing treatment with pegylated interferon‐alpha and ribavirin. Issue 9 (13th November 2013) - Striki, A.; Manolakopoulos, S.; Deutsch, M.; Mela, M.; Kalafateli, M.; Schini, M.; Anagnostou, O.; Triantos, C.; Andreadis, I.; Ketikoglou, I.; Papatheodoridis, G.; Pectasides, D.
Summary Peginterferon‐alpha (PegIFNa) frequently causes neutropenia, mainly due to bone marrow suppression. The aim of this study was to explore factors that are associated with infections during antiviral treatment. We analysed data from 275 chronic hepatitis C (CHC) patients with compensated liver disease who underwent 318 courses of PegIFNa and ribavirin. Neutropenia was defined as neutrophils <1000 cells/μL. Mean leucocytes count significantly decreased from baseline to treatment nadir (7081 ± 2182 vs 3293 ± 1331 cells/μL, P < 0.001), while neutropenia was observed in 32% during treatment. Thirty‐one infections were observed. The incidence rate for infection was assessed at 1.46 infections per 100 person‐months of therapy. The hazard rate for infection did not correlate with the neutrophils' nadir or the decrease in white blood cells. In multivariate Cox's regression analysis, cirrhosis was the only factor that was significantly associated with the occurrence of infection. Our data show that the development of bacterial infections during treatment with PegIFNa and ribavirin in patients with compensated CHC is not associated with reduction or the nadir of white cells or neutrophil counts. Baseline cirrhosis is the only factor related with infection during treatment. The common practice of dose adjustment or discontinuation of interferon should be revised; careful assessment of liver damage before therapy and close monitoring during therapy are essential in all patients receiving interferon‐based regimes, to minimize the detrimental consequences of infections.